Saussurea yilingii (Asteraceae, Cardueae), a new species from Sichuan, China - Chen, You-Sheng (Phytotaxa, 2020)
Saussurea yilingii, a new species from Muli county, Sichuan province of China, is described and illustrated. It is similar to the species of snow lotus in habit, odour, and dark brown phyllaries but is lacking membranous colourful upper leaves which are typical for Saussurea subgen. Amphilaena. The new species is assessed as Critically Endangered (CR) according to IUCN Red List Categories and Criteria.